SOCIO EDUPRENENUR SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN DI INDONESIA - Hadi Ismanto; Vembri Aulia Rahmi (Jurnal Riset Entrepreneurship, 2020)
Additional learning or tutoring is urgently needed to help improve learning but due to high costs, some communities, especially those in the middle to lower economic level, are unable to register their children to attend tutoring (additional tutoring). The existence of Socioedupreneur is an alternative solution for those who do not have the cost to experience tutoring. Paying sincerely or not at all can alleviate them in terms of costs and can show the importance of education for the future and instill that all have the right to receive the same education. This research was conducted to determine the role of socio edupreneur in improving the quality of education. The purpose of this study was to determine the role of socio edupreneur as an effort to improve the quality of education in Indonesia. The method used by researchers in this study uses qualitative research methods, this type of research is descriptive qualitative research, a case study approach that is an approach to study, explain or interpret a case. In essence, this study seeks to highlight a decision or set of decisions or set of decisions why the decision was taken, how it was implemented, and what the results were. This research intensively focuses on an object that is about how the role of socioedupreneur in improving the quality of education.